Keeping Food Safe: Choosing and Using Food Thermometers in Homes - Claudia L. Peñuela; Amy Simonne; Isabel Valentin-Oquendo (EDIS)
Proper cooking of foods to safe internal temperatures is one of the most effective ways to prevent foodborne illnesses. Several types of food thermometers are available for purchase and choosing the right one when cooking at home will help to keep food safe for your family. This revised 3-page fact sheet provides specific information on how to use different thermometers in different foods. Written by Claudia L. Peñuela, Amy Simonne, and Isabel Valentin-Oquendo, and published by the UF Department of Family, Youth and Community Sciences, March 2012.